Transcriptome analysis of classical blood cells reveals downregulation of pro-inflammatory genes in the classical monocytes of long COVID patients - Fricke, Florian; Mai, Franz; Wossidlo, Christine; Steinbeck, Felix; Bergmann-Ewert, Wendy; Kordt, Marcel; Kraft, Karin; Müller, Britta; Reisinger, Emil C.; Müller-Hilke, Brigitte (Frontiers in Immunology, 2025)
IntroductionDespite extensive research, the pathogenesis and predispositions underlying long COVID (long-term coronavirus disease 2019) remain poorly understood.MethodsTo address this, we analyzed the immunological landscapes of 44 patients with long COVID and 44 matched convalescents using single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells (PBMCs) and validated the findings with plasma cytokine measurements via Luminex technology.ResultsWhile the immune cell compositions showed minimal quantitative differences only among natural killer (NK) cells, the transcriptome analyses identified distinct gene expression patterns, particularly in classical monocytes: patients with long COVID exhibited downregulation of the inflammation-associated genes, including IL1B and CXCL2. Imputation of the transcription factor activity hinted at a reduced inflammasome activity (via SNAI1) and an impaired monocyte differentiation (via ATF2) in long COVID. The RNA velocity data supported the presence of immature classical monocytes in these patients.DiscussionThese findings show that monocytes might be dysregulated and/or exhausted in patients with long COVID.